PENGARUH KINERJA PERUSAHAAN, CORPORATE GOVERNANCE, DAN SHAREHOLDER PAYOUT TERHADAP KOMPENSASI EKSEKUTIF Studi Kasus Pada Perusahaan Non Financial yang Terdaftar di Bursa Efek Indonesia Tahun 2007-2010 - Mardiyati, Umi; Devi, Monica Shinta; Suherman, Suherman (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
The purpose of this study is to know the effect of firm performance, corporate governance, and shareholder payout on executive compensation by using firm size as control variable. Firm performance measured by Return On Asset (ROA), Net Profit Margin (NPM), and Earning Per Share (EPS). Corporate governance measured by institutional shareholding. And shareholder payout measured by dividend yield. The research model in this study used panel data analysis. The samples are 121 non financial firms listed in Indonesia Stock Exchange during the period 2007-2010 which is taken by purposive sampling method. Based on the correlation, the empirical result shows that firm performance measured by ROA, NPM, and EPS have positive effect and significantly to executive compensation. Afterwhile, institutional shareholding and dividend yield have no positive effect significantly to executive compensation. Besides that, the results indicate that company size is the major determinant of compensation Key words: ROA, NPM, EPS, Institutional Shareholding, Dividend Yield, Cash Compensation, Firm Size, Non Financial Firm